2016
DOI: 10.1007/s12035-016-9971-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Single Nucleotide Polymorphisms of Base Excision Repair Genes on DNA Damage and Efficiency of DNA Repair in Recurrent Depression Disorder

Abstract: Elevated level of DNA damage was observed in patients with depression. Furthermore, single nucleotide polymorphisms (SNPs) of base excision repair (BER) genes may modulate the risk of this disease. Therefore, the aim of this study was to delineate the association between DNA damage, DNA repair, the presence of polymorphic variants of BER genes, and occurrence of depression. The study was conducted on peripheral blood mononuclear cells of 43 patients diagnosed with depression and 59 controls without mental diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…PARP1 is responsible for posttranslational modification of nuclear proteins in response to various types of DNA damage as well as oxidative stress (Muiras et al, 1998;Beneke and Bürkle, 2007). With an essential role in base excision repair (BER) and double strand break (DSB) repair, PARP1 has been known as the "sensor of nicks" within DNA (Mao et al, 2011;Czarny et al, 2017). Comparative studies among 13 mammalian species found that the enzymatic activity of PARP1 positively correlates with maximum lifespan in various mammals, including humans (Bürkle et al, 1992;Muiras et al, 1998;Piskunova et al, 2008;Noren Hooten et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…PARP1 is responsible for posttranslational modification of nuclear proteins in response to various types of DNA damage as well as oxidative stress (Muiras et al, 1998;Beneke and Bürkle, 2007). With an essential role in base excision repair (BER) and double strand break (DSB) repair, PARP1 has been known as the "sensor of nicks" within DNA (Mao et al, 2011;Czarny et al, 2017). Comparative studies among 13 mammalian species found that the enzymatic activity of PARP1 positively correlates with maximum lifespan in various mammals, including humans (Bürkle et al, 1992;Muiras et al, 1998;Piskunova et al, 2008;Noren Hooten et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a deficiency of the vitamins causes a shifting of the balance between these two nucleoside monophosphates towards dUMP resulting in the incorporation of uracil into DNA (Reynolds, 2014). This, together with the impairment of DNA damage repair discovered by our team, that can be, at least partly, attributed to the presence of specific SNP variants, may lead to the introduction of AP sites or DNA strand breaks and apoptosis of neurons, especially in the hippocampus (Young et al 2007;Czarny et al, 2017a). In addition, folate deficiencies are also known to affect mtDNA, causing inter alia an increased number of deletions and thus the induction of oxidative stress (Chou and Huang, 2009;Chou et al, 2007;Kronenberg et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…An elevated level of DNA damage was observed in patients with depression. Furthermore, single nucleotide polymorphisms of BER genes may modulate the risk of this disease [ 106 ]. DNA damage and DNA repair also participate in the etiopathology of schizophrenia and autism spectrum disorders [ 45 ].…”
Section: Nucleusmentioning
confidence: 99%